2006
DOI: 10.1002/path.2055
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen status of lung granulomas in Mycobacterium tuberculosis‐infected mice

Abstract: It is often assumed that Mycobacterium tuberculosis (Mtb)-induced granulomatous lesions, particularly those undergoing central caseation, are anoxic, and that the survival of Mtb in these lesions requires the integrity of its non-oxidative respiratory pathways. Using the hypoxia marker pimonidazole, we now provide immunohistochemical evidence that in the most frequently used animal model system of inbred mice Mtb-induced granulomas, even after more than one year of aerogenic infection, are not severely hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
4

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(165 citation statements)
references
References 52 publications
11
150
4
Order By: Relevance
“…However, growing evidence has revealed that the extent of hypoxia associated within a given host varies widely based on the size, location, and composition of the microenvironment (31)(32)(33). Our studies modeled quiescent M. tuberculosis using an O 2 environment of 1%, but the metabolic principle revealed may have broader significance, namely, the ability of succinate to serve as a biochemical bridge between oxidative and fermentative metabolic states.…”
Section: Discussionmentioning
confidence: 99%
“…However, growing evidence has revealed that the extent of hypoxia associated within a given host varies widely based on the size, location, and composition of the microenvironment (31)(32)(33). Our studies modeled quiescent M. tuberculosis using an O 2 environment of 1%, but the metabolic principle revealed may have broader significance, namely, the ability of succinate to serve as a biochemical bridge between oxidative and fermentative metabolic states.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether Mtb might be the source, we infected macrophages with a strain of Mtb lacking narG. The mutant strain grows normally in aerobic culture and is as virulent as WT Mtb in mice (17,19) but cannot respire nitrate. Macrophage cultures infected with ΔnarG Mtb accumulated no nitrite, whereas infection with a mutant strain complemented with the WT narG allele led to accumulation of as much nitrite as infection with WT Mtb (Fig.…”
Section: Mtb Respires Nitrate In Human Macrophages Cultured At Nonhypmentioning
confidence: 99%
“…In the host, Mtb is thought to survive over decades in hypoxic sites (17,18). When oxygen is scarce, Mtb reduces nitrate (NO 3 − ) to nitrite (NO 2 − ) as a means to maintain redox homeostasis and energy production (19).…”
mentioning
confidence: 99%
“…138 The caseum is predominantly composed of host-derived lipids, and a recent analysis of gene regulation in the immediately surrounding cells shows Mtb-driven dysregulation of host lipid metabolism. 117 The granuloma environment is considered hypoxic in guinea pigs, rabbits, nonhuman primates, and human beings, 5,213 which is an important consideration for mycobacterial metabolism and antibiotic therapy efficacy. It was previously believed that Mtb were sparse in the caseum, based on Ziehl-Neelsen acid-fast staining, with most of the detectable bacilli persisting at the periphery.…”
Section: Pathogenesis and Lesion Developmentmentioning
confidence: 99%